2016
DOI: 10.1055/s-0042-108058
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Metabolite Profiles of Cannabis sativa L. Trichomes during Flowering Period Using 1H NMR-Based Metabolomics and Real-Time PCR

Abstract: Cannabis sativa trichomes are glandular structures predominantly responsible for the biosynthesis of cannabinoids, the biologically active compounds unique to this plant. To the best of our knowledge, most metabolomic works on C. sativa that have been reported previously focused their investigations on the flowers and leaves of this plant. In this study, 1H NMR-based metabolomics and real-time PCR analysis were applied for monitoring the metabolite profiles of C. sativa trichomes, variety Bediol, during the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…THCAS and CBDAS levels in trichomes in flowers were described as stable during the latter stages of floral development in the C . sativa strain Bediol [ 43 ]. These authors also reported higher levels of THCAS and CBDAS in leaves versus flowers or flower trichomes, which is quite the inverse of the results reported here for four separate strains of Cannabis (Figs 7 and 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…THCAS and CBDAS levels in trichomes in flowers were described as stable during the latter stages of floral development in the C . sativa strain Bediol [ 43 ]. These authors also reported higher levels of THCAS and CBDAS in leaves versus flowers or flower trichomes, which is quite the inverse of the results reported here for four separate strains of Cannabis (Figs 7 and 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The resin inside glandular trichomes of C. sativa, the apoplast of glandular scales in R. dauricum, and oil bodies in R. marginata are the storage environments and sites of the oxycyclase-catalyzed last step in the synthesis of cannabinoids [5,37,40,97]. 1 H NMR-based metabolomics of C. sativa trichomes revealed co-storage of the cannabinoids with an abundance of sugars, amino acids, choline, organic acids, and terpenes [5]. Sugars, choline, and organic acids are typical constituents that, when present in appropriate stoichiometric ratios, form natural deep eutectic solvents (NADESs) [139].…”
Section: Possible Storage Of High Amounts Of Cannabinoids In Natural mentioning
confidence: 99%
“…NMR is recognized as an untargeted powerful tool [19,20] to give a complete metabolite profile of biological matrixes. Up to now, the NMR based metabolomic investigations regarding C. sativa L. have been focused on the study of plant tissues such as trichomes [21], cell suspensions [22] and inflorescences [23]. Only a partial assignment of the inflorescence NMR spectra is available in literature [23,24].…”
Section: Chemical Profile Of Hemp Inflorescencesmentioning
confidence: 99%